Determinants of Halal Meat Purchase Intention: Extending the Theory of Planned Behavior with Halal Supply Chain Knowledge and Religiosity - Amalia Istivani; Moh Farid Najib (Politeknik Negeri Bandung, 2026)
The Indonesian market for halal products, especially meat distributed through traditional marketplaces, is characterized by notable intricacy. This research seeks to identify the key factors influencing consumers’ willingness to purchase halal meat within this context. The study is grounded in the Theory of Planned Behavior (TPB) and further incorporates elements such as individual religiosity and awareness of the halal supply chain. This awareness includes knowledge of compliant slaughtering procedures, proper handling and distribution practices, and labeling standards. A causal, quantitative methodology was adopted, with data gathered via an online questionnaire from 403 participants and subsequently analyzed using SmartPLS. The findings reveal that all TPB dimensions—attitude, subjective norms, and perceived behavioral control—affect purchase intention. Moreover, understanding of halal slaughtering practices and logistics management shows a meaningful influence, while awareness of halal labeling does not demonstrate a statistically significant effect.